2017 Elijah High-Altitude Balloon Launch Team Summer Proceedings Report - Bock, Quinlan Jackson; Davitz, Taylor; Furey, Josh; Rasmussen, Tyler (Proceedings of the Wisconsin Space Conference, 2018)
The 2017 Wisconsin Space Grant Consortium Elijah High-Altitude Balloon Launch Team was comprised of one student from Lawrence University, two students from the Milwaukee School of Engineering, and one student from the University of Wisconsin – Fox Valley. This year, three members of the team had experience with high altitude balloon launches due to previous participation on either the Elijah Payload or Launch Team, or both. A training session was hosted by Dr. Farrow to familiarize or refresh the team with the physical setup of a launch train as well as how to run track predictions and how to read the jet stream charts. Launches were planned and carried out for the Elijah High-Altitude Balloon Payload Team. This launch was successful, reaching a peak altitude of over 115,000 ft (35 km) above mean sea level.